2020
DOI: 10.1038/s41598-020-61655-2
|View full text |Cite
|
Sign up to set email alerts
|

Facile generation of giant unilamellar vesicles using polyacrylamide gels

Abstract: Giant unilamellar vesicles (GUVs) are model cell-sized systems that have broad applications including drug delivery, analysis of membrane biophysics, and synthetic reconstitution of cellular machineries. Although numerous methods for the generation of free-floating GUVs have been established over the past few decades, only a fraction have successfully produced uniform vesicle populations both from charged lipids and in buffers of physiological ionic strength. In the method described here, we generate large num… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
30
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 23 publications
(31 citation statements)
references
References 46 publications
(79 reference statements)
1
30
0
Order By: Relevance
“…The distribution of GUV diameters ranges from ~1 μm to ~40 μm. In our measurements, the mean diameter for various PAA stiffness and porosity conditions was on the order of 10 μm(Parigoris et al, 2020).…”
mentioning
confidence: 70%
See 1 more Smart Citation
“…The distribution of GUV diameters ranges from ~1 μm to ~40 μm. In our measurements, the mean diameter for various PAA stiffness and porosity conditions was on the order of 10 μm(Parigoris et al, 2020).…”
mentioning
confidence: 70%
“…Polyacrylamide formulations were adapted from those used in Wen et al, 2014. To start, we recommend using formulation 1 or 5. b. We have found that the variations in PAA stiffness and pore size do not significantly affect the concentration and size distribution of the free-floating GUVs that are generated (Parigoris et al, 2020 2. Loosen the lid on the conical tube and place it in the desiccator/vacuum.…”
Section: Notesmentioning
confidence: 85%
“…Here, using polymer assisted swelling 4851 and electroformation 52 methods, we compare the produced GUVs on vesicle properties important for investigating MPs in GUVs as outlined above. We compare the ability of these formation methods to produce a high number of vesicles with diameters between 5 – 20 µm under physiologically relevant conditions and characterize whether immobilization using the biotin-streptavidin system was affected by the presence of salt.…”
Section: Introductionmentioning
confidence: 99%
“…Surface-assisted assembly, a growing collection [22][23][24][25][26][27][28][29][30] of techniques in which solvent-free lipid films are templated onto surfaces and then hydrated in aqueous solutions, is a highly promising route to obtain giant vesicles 1,2 . In the earliest discovered technique 22,23 , contemporarily known as 'gentle hydration' 1,2 , dry lipid films are templated onto impermeable glass and Teflon surfaces and then hydrated in quiescent solutions.…”
Section: Introductionmentioning
confidence: 99%
“…Electroformation modifies the procedure by applying an electric field normal to lipid films templated on conductive surfaces 24,25 . Other recent modifications include gel-assisted hydration, where lipid films are templated onto soluble hydrogels supported on glass surfaces [26][27][28] and PAPYRUS, Paper-Abetted amPhiphile hYdRation in aqUeous Solutions, where lipid films are templated onto insoluble fibers of cellulose filter paper 29 and fabrics 30 composed of natural, semi-synthetic, and synthetic fibers.…”
Section: Introductionmentioning
confidence: 99%